PENGARUH REKRUTMEN, SELEKSI, DAN PENEMPATAN KERJA TERHADAP PRODUKTIVITAS KERJA PADA PT. XYZ - Syahrian; Rayhan Widyadhana Darmawan (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
Abstract: Work Productivity is one aspect that plays an important role in the development of a company or organization. In this study, its aims to test the influence between work productivity and recruitment, selection, work placement on employees of PT. XYZ. In this study, used questionnaires to collect data. The sample in this study was 69 employees. The sampling technique in this study used a Nonprobability Sampling method with the saturation sampling. The data analysis method used is multiple linear regression. The analytical data used in this study used classical assumption tests, normality tests, model tests, and hypothesis tests. The results of the analysis in this study indicate that recruitment, selection, and work placement have an influence on work productivity. So that PT. XYZ needs to pay attention to the level of recruitment, selection, and work placement as an effort to improve work productivity.